Altering the solubility of metal–organic polyhedra via pendant functionalization of Cp3Zr3O(OH)3 nodes. Issue 2 (13th December 2022) - Sullivan, Meghan G.; Sokolow, Gregory E.; Jensen, Eric T.; Crawley, Matthew R.; MacMillan, Samantha N.; Cook, Timothy R.
Abstract : A new method to tune solubility of ZrMOP s via node-modification. Abstract : The chemistry of zirconium-based metal-organic polyhedra (ZrMOP s) is often limited by their poor solubilities. Despite their attractive features—including high yielding and facile syntheses, predictable topologies, high stability, and tunability—problematic solubilities have caused ZrMOP s to be under-studied and under-applied. Although these cages have been synthesized with a wide variety of carboxylate-based bridging ligands, we explored a new method for ZrMOP functionalization via node-modification, which we hypothesized could influence solubility. Herein, we report ZrMOP s with benzyl-, vinylbenzyl-, and trifluoromethylbenzyl-pendant groups decorating cyclopentadienyl moieties. The series was characterized by 1 H/ 19 F NMR, high-resolution mass spectrometry, infrared spectroscopy, and single-crystal X-ray diffraction. The effects of node functionalities on ZrMOP solubility were quantified using inductively coupled plasma mass spectrometry. Substitution caused a decrease in water solubility, but for certain organic solvents, e.g. DMF, solubility could be enhanced by ∼20×, from 16 μM for the unfunctionalized cage to 310 μM for the vinylbenzyl- and trifluoromethylbenzyl-cages.